148. Imipenem-Relebactam activity and genotypic characteristics of Carbapenem-resistant Enterobacterales and Pseudomonas aeruginosa Isolates from Latin American Infections - Study for Monitoring Antimicrobial Resistance Trends (SMART) 2017 – 2020. (15th December 2022) - Mizuno, Gustavo; Polis, Thales; Ferrari, Jacqueline; Pavia, Jacqueline; Beirão, Elisa; Gales, Ana C; Tuon, Felipe; Alcantara, Alexandre; Batista, Paula M
Abstract: Background: Imipenem/relebactam (IMI/REL) is a combination of Imipenem with Relebactam, an inhibitor of class A and C β-lactamases and has been approved in the US and EU, but not in Latin America. This report evaluates the in vitro activity of IMI/REL and comparators against Latin America (LATAM) Enterobacterales and P. aeruginosa (PSA) and the frequency of carbapenemase encoding genes (CEG) among gram-negative bacilli (GNB) isolated through the SMART Program (2017-2020). Methods: 21606 nonconsecutive GNB isolates were collected in 10 LATAM countries. MICs for amikacin (AK), ceftazidime-avibactam (C-A), ceftolozane/tazobactam (C/T) and IMI/REL were determined by broth microdilution and interpreted by CLSI; a subset of Enterobacterales and P. aeruginosa carbapenem resistant was selected for characterization of carbapenemase encoding genes by PCR followed by DNA sequencing. Results: Escherichia coli (N=9872; EC) tested susceptible to > 96% of all antibiotics analyzed; for P. aeruginosa (N=4528), C/T and C-A had the best susceptibility rates (85.7 and 86.6% respectively); for Enterobacter cloacae (N=1091; ECL) and Klebsiella pneumoniae (N=6115; KPN), we note that only IMI/REL and C-A were ≥ 95%. Profile of 2845 carbapenem resistant isolates was analysed and the main isolated agent in most countries was KPN, corresponding to 55% (1470), except in Mexico, Panama and Venezuela where PSA was the main carbapenemase producer. The bla kpc-2, 3 were found in KPN 76.7, 79.2, 53.3, 52.1 and 85.3% in Argentina, Brazil, Colombia, Ecuador and Puerto Rico, respectively; Guatemala, Mexico, Venezuela presented bla NDM-1 in 74.3, 44.1 and 51.4%. Among ECL bla kpc-2 (35.7%-Brazil, 48.2%-Colombia) and bla NDM-1 (45.7%-Mexico) were most frequent, bla VIM-24 (16.6%) and bla IMP-18 (38.8%) were observed in Venezuela and Puerto Rico and in the latter, we observed first time reported bla kpc-45 in 27.7 %. PSA expressed bla kpc-2 (33.33%- Colombia), Chile and Venezuela bla VIM-2 (44.3%, 58.8%); bla spm-1 occurred only in Brazil (6.9%). Most common carbapenemase-producing bacteria in LATAM (n=2845) Antimicrobial susceptibility of Enterobacterales and P. aeruginosa (full data analysis=21606) Most Frequent CEG detected among carbapenemase producing isolates in Latin American countries (Genotypical sample analyzed n=2845) Conclusion: The frequency of CEG is a threat in LATAM, mostly in Enterobacterales, whereas PSA as expected, has a lower frequency, but still a concern. In LATAM, IMI/REL has shown relevant activity against CEG producers, showing it is an option for treatment infections caused by MDR strains. Disclosures: Gustavo Mizuno, PharmD, MSD Brazil: Employee Thales Polis, MD, MSD Brazil: Employee Jacqueline Ferrari, MD, MSD Brazil: Employee Jacqueline Pavia, MD, MSD COLOMBIA: EMPLOYEE Elisa Beirão, MD, MSD BRAZIL: Grant/Research Support Ana C. Gales, MD, MSD BRAZIL: Grant/Research Support Felipe Tuon, MD, MSD BRAZIL: Grant/Research Support Alexandre Alcantara, PharmD, MSD BRAZIL: EMPLOYEE Paula M. Batista, PharmD, MSD BRAZIL: EMPLOYEE.